Zygoribatula colemani sp. nov (Acari, Oribatida, Oribatulidae) from Granite Outcrops in Georgia, USA, with a highly variable translamella - Franklin, Elizabeth; Norton, Roy. A.; Crossley, Jr., D. A. (Zootaxa, 2008)
The oribatid mite Zygoribatula colemani sp. nov. (Oribatulidae) is described and illustrated based on adults collected from shallow soils in depression pits found in granitic outcrops of the Piedmont Plateau in Georgia (USA). By definition, members of Zygoribatula always possess a translamella on the prodorsum, the only feature distinguishing this genus from Oribatula. But Z. colemani shows a full range of variation, from having the translamella well developed to entirely absent; this brings the distinction of these genera into question and points out the need for a careful revision of generic concepts in Oribatulidae. Depending on the specimens examined, Z. colemani could be placed in either genus, but we tentatively include it in Zygoribatula, since in some specimens the translamella is complete and well delineated. A tentative diagnostic key to differentiate the species of Zygoribatula previously reported in the USA is included.